Literature Review on Public Transport and Land Use: Based on CiteSpace Statistical Analysis - Yinjie He; Biao Liu; Chengyou Xu; Dafang Wu (Land)
With the growing demand for mobility fueled by global population expansion and rapid urbanization, the intricate interplay between public transport and land use, along with their economic, environmental, and social externalities, has emerged as a critical concern for policymakers and the public alike. This study assembles publicly available academic literature, including papers, reports, books, and news articles, to construct a comprehensive database. Using CiteSpace 5.8.R3 software, this study conducts a visualized analysis of 10,470 scholarly works on public transport and land use published since 1932, identifying and synthesizing the researcher, research stages, research theories, research models, and research hotspots. Findings reveal that since Mitchell and Rapkin first introduced the transport–land use relationship in 1954, research in this field has steadily gained traction, particularly after the 1973 oil embargo crisis. The Journal of Transport and Land Use and institutions such as the University of Minnesota’s Transportation Research Center have played pivotal roles, particularly with the establishment of the World Society for Transport and Land Use Research (WSTLUR). In recent years, China’s high-speed rail expansion has further revitalized interest in this field. Prominent scholars in this domain include Robert Cervero, Reid Ewing, Michael Duncan, and Peter Calthorpe. Major theoretical frameworks encompass utility theory, urban economic theory, and the human–land system theory. Key modeling approaches include the spatial interaction model, the stochastic utility model, and urban economic models. Current research hotspots center on safety and public health, equity and valuation, environmental sustainability and energy efficiency, as well as transit-oriented development (TOD) and accessibility. This systematic literature review offers valuable insights to inform land use planning, enhance spatial structure, guide transportation project decision making, and optimize transport infrastructure and service provision.